Sitagliptin ameliorates L-arginine-induced acute pancreatitis via modulating inflammatory cytokines expression and combating oxidative stress - Eltahir, Heba M.; Elbadawy, Hossein M.; Almikhlafi, Mohannad A.; Alalawi, Ali M.; Aldhafiri, Ahmed J.; Alahmadi, Yaser M.; Al thagfan, Sultan S.; Albadrani, Muayad; M Eweda, Saber; Abouzied, Mekky M. (Frontiers in Pharmacology, 2024)
Background: Acute pancreatitis (AP) is an inflammatory condition that resolves spontaneously, but occasionally, develops into systemic inflammation, organ failure and mortality. Oxidative stress and activation of inflammatory pathways represent major players in AP pathogenesis. Current management of AP relies on attenuating injuries to the pancreas and putting the inflammatory process under control. In this study, we investigated the role of sitagliptin in modulating L-arginineinduced AP in rats.Methods: swiss rats were subdivided into a healthy control group, AP group (a single dose of Larginine 250 mg/100g, intraperitoneal), and sitagliptin+L-arginine-treated group (10mg sitagliptin/kg body weight/day, orally). Sitagliptin treatment started one hour after L-arginine injection and continued for 3days. Biochemical and histopathological investigations were performed on serum and tissue samples collected from test animals.Results: L-arginine increased pancreatic meyloperoxidase and serum amylase-and lipase activities and serum levels of TNF-α, LT-α, IFN-γ, IL-1α/β, IL-6, IL-10, IL-12, and IL-15. AP animals showed elevated MDA and NO and decreased GSH and serum calcium levels. histopathological changes were observed by H&E staining. Sitagliptin treatment significantly ameliorated these biochemical and histological changes diminishing the signs of AP.Sitagliptin treatment was effective in ameliorating L-arginine-induced AP which can be regarded to its anti-inflammatory and antioxidant effect.